Effect of exogeneous enzymes on performance of finishing cattle fed sorghum-based diets - Kiselewski, Elizabeth Renee (My University, 2025)
Interest in water conservation efforts has resulted in increased interest in grain sorghum. One limitation to sorghum utilization is it decreased digestibility compared to corn. Mitigating this challenge was the motivation for the following evaluations. A finishing study examining Pyramid PowerGrow Ruminant (Pyramid Feeds, Scott City, KS) paired with an in vitro experiment examining four differing protease enzymes. The finishing experiment utilized 280 crossbred steers (441.74 kg ± 15.19 kg initial body weight) to evaluate nutrient digestibility, feedlot performance, and carcass characteristics. Steers were randomly allocated to 36 feedlot pens containing 7 (8 pens) or 8 (28 pens) animals per pen. Pens were randomly assigned to one of two dietary treatments within blocks (18 blocks). Cattle were randomly assigned to a pen within each block by chute order, two pens were filled at a time. The finishing diet consisted of 59.62% ground sorghum, 25% sorghum-based dried distillers grains with solubles, 12% corn silage, 3.38% supplement. Ground corn was utilized as the carrier for the supplement; within the enzyme groups supplement Pyramid PowerGrow Ruminant was used in lieu of the ground corn. Cattle were fed once daily in the morning, ad libitum, and daily feed bunk scores were taken to determine feed allocation. On day 67, fresh fecal pats were collected from the pen surface and analyzed for protein, starch, neutral detergent fiber (NDF), ash, organic matter, and acid detergent insoluble ash concentrations. After 148 days on feed, steers were harvested, and after 96 h of refrigeration carcass data were collected. Data were analyzed as mixed models with diet as the fixed effect, pen as the experimental unit, and block as the random effect. There were numerical but non-significant (P > 0.10) differences between treatments for feedlot performance, nutrient digestibility, and carcass characteristics. Final body weight of the enzyme treatment was 5.4 kg heavier than the control treatment. Starch digestibility was marginally higher but not significantly different in the enzyme group compared to the control group (91.26% vs. 89.58%). Marbling score was 15.8 points higher in the control treatment compared to the enzyme treatment. The in vitro experiment evaluated effects of four protease enzymes on in vitro dry matter digestibility (IVDMD), terminal pH, volatile fatty acid (VFA) production, and methane production per gram of substrate digested. Liquipanol (liquid papain derived from carica papaya L.), fungal protease, fungal neutral protease, and fungal acid proteases were examined when added to sorghum at a rate of 3 or 30 [mu]L per tube. There were 11 treatments, 9 of which utilized sorghum as a substrate, those treatments were fungal acid protease 3 and 30 [mu]L per 50-mL tube, fungal protease 3 and 30 [mu]L per 50-mL tube, fungal neutral protease 3 and 30 [mu]L per 50-mL per tube, Liquipanol 3 and 30 [mu]L per 50-mL tube, and sorghum no enzyme. There was also a corn no enzyme and a blank treatment. The fungal acid protease, fungal protease, fungal neutral protease, and Liquipanol treatments all utilized sorghum as the substrate. A randomized complete block design was utilized to evaluate the 11 treatments including a control corn and sorghum treatment and nine blocks. Terminal pH, IVDMD, and VFA profiles were analyzed as mixed models with treatment as the fixed effect and run and block within run as random effects. The control corn treatment had the lowest pH, and greatest IVDMD, and greatest VFA production compared to the sorghum-based treatment groups (P < 0.01). The results of these two experiments indicate that protease enzyme supplementation results in modest but statistically insignificant differences in sorghum digestibility.
Keywords: Feedlot; Sorghum; Protease enzymes; In Vitro